2021
DOI: 10.1542/peds.2020-011528
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Developmental Delay in Infants and Toddlers With an FMR1 Mutation

Abstract: BACKGROUND: Children with FMR1 gene expansions are known to experience a range of developmental challenges, including fragile X syndrome. However, little is known about early development and symptom onset, information that is critical to guide earlier identification, more accurate prognoses, and improved treatment options. METHODS: Data from 8 unique studies that used the Mullen Scales of Early Learning to assess children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Given the adjacency of P1 and N1 sources in the auditory cortex (Yvert et al, 2005), we expect a similar temporal-to-central developmental trajectory in the topographical pattern of P1 in children. With this hypothesis, the findings in this study might have reflected a delayed development of the auditory brain in children with FXS, which is part of the global developmental delay known in this population (Roberts et al, 2016; Wheeler et al, 2021). Either interpretation points to the fact that children with FXS may have altered (impaired or delayed) auditory processing than their age-matched TD peers.…”
Section: Discussionmentioning
confidence: 73%
“…Given the adjacency of P1 and N1 sources in the auditory cortex (Yvert et al, 2005), we expect a similar temporal-to-central developmental trajectory in the topographical pattern of P1 in children. With this hypothesis, the findings in this study might have reflected a delayed development of the auditory brain in children with FXS, which is part of the global developmental delay known in this population (Roberts et al, 2016; Wheeler et al, 2021). Either interpretation points to the fact that children with FXS may have altered (impaired or delayed) auditory processing than their age-matched TD peers.…”
Section: Discussionmentioning
confidence: 73%
“…Learning objectives are based on each infant’s developmental profile of strengths and areas of weakness, with focus in domains that are related to social learning and social-cognitive development, including verbal and nonverbal language, social orienting, and joint attention. Learning objectives also include a focus on motor development, as this is often one of the first symptoms reported by parents of infants with the target NGCs (15), and delays in motor skills often lead to delays in communication. Learning objectives are targeted during each session and embedded into the practice and reflection activities.…”
Section: Methodsmentioning
confidence: 99%
“…Delay in fine motor development is obvious at as early as 9 months of age (Roberts et al, 2019). Nevertheless, boys could continue to acquire motor skills in early infancy at a rate that was approximately half of the rate of their normally developing peers, and girls exhibited development at a rate that was approximately 75% of that of their typically developing counterparts (Wheeler et al, 2021).…”
Section: Motor Skill Deficits In Fxsmentioning
confidence: 99%
“…FXS patients often have difficulty in coordinating both fine motor and gross motor skills; however, the degree of difficulty varies significantly across individuals. Data from eight unique studies with 1178 observations of more than 500 young children showed that 6-month-old boys with full Fmr1 gene mutations had delays in motor skill development (Wheeler et al, 2021). Delay in fine motor development is obvious at as early as 9 months of age (Roberts et al, 2019).…”
Section: Motor Skill Deficits In Fxsmentioning
confidence: 99%